1984
DOI: 10.1159/000153469
|View full text |Cite
|
Sign up to set email alerts
|

<i>&alpha;</i>-<i>L</i>-Fucosidase Polymorphism in Human Semen, Blood, and Vaginal Fluid

Abstract: The diallelic enzyme α-L-fucosidase has been found to be highly active in semen. Eight distinct enzyme bands were observed in each homozygote and the heterozygote consisted of a combination of bands. The isoelectric points ranged between pI 4.34 and 6.65. Activity was found to be much lower in vaginal fluid, not more than three cathodal bands were visible in any sample examined. In leucocytes, 5 bands were detected in homozygotes whilst in serum only two faint anodal bands could be detected. Activity was low i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Eiberg et al [1984], Kompf and Ritter [1983] and Olaisen et al [1983] for FI3A, and Gill and Sutton [1984] and Kompf and Ritter [1983] for FUCAI. Tables 2 and 3 summarize the results of the formal analysis undertaken on mother/child pairs, and tables 4 and 5 present data on familial segregation.…”
Section: Resultsmentioning
confidence: 99%
“…Eiberg et al [1984], Kompf and Ritter [1983] and Olaisen et al [1983] for FI3A, and Gill and Sutton [1984] and Kompf and Ritter [1983] for FUCAI. Tables 2 and 3 summarize the results of the formal analysis undertaken on mother/child pairs, and tables 4 and 5 present data on familial segregation.…”
Section: Resultsmentioning
confidence: 99%
“…(EC 3.2.1.51). Previously a-L-fucosidase has been purified from epididymal tissue (Carlsen & Pierce, 1972) and the polymorphism of the enzyme has been identified in human semen (Gill & Sutton, 1984). Recently, Srivastava et al (1986) purified a-L-fucosidase from bovine seminal plasma and demonstrated its role in the acrosome reaction of spermatozoa.…”
Section: Fractionmentioning
confidence: 99%